HALAL AND THAYYIB FOOD IN ISLAMIC SHARIA PERSPECTIVE - Ali Farkhan Tsani; Hadi Susilo; Suyamto Suyamto; Usman Setiawan; Sudanto Sudanto (Universitas Mathla’ul Anwar Banten, 2021)
Consumption of halal and thayyib food will make it easier for someone to do good deeds, this is mentioned in the Qur'an Surah Al Maidah verse 88. Halal is goods that are not haram, consuming them is not prohibited by religion. At least, the prohibition can be divided into two aspects. First, haram in essence or materially has been declared haram by the Shari'a, such as pigs, carrion, and blood. Second, haram is not in essence, but can be from the way of buying, obtaining, or processing the goods. Thayyib means something that is holy, not unclean, and not disgusting which is not liked by the soul. Whoever eats unlawful food, whether he wants it or not, his limbs will tend to sin, whether he realizes it or not. Whoever eats halal food, surely his limbs will obey and be given God’s guidance to do good.